1994
DOI: 10.1177/009365094021001006
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Attitudinal Components to Trust in Media

Abstract: Past research has proposed that the receiver's relationship to the content of a message will affect credibility attributed to the source. Current literature proposes explanatory mechanisms that require empirical distinctions among the various components of attitude, yet researchers often employ measures of “attitude extremity” that confound these components. This study follows Guttman's mathematical theory of attitude and its distinctions between four attitude components: direction, intensity, closure, and inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 8 publications
0
25
0
1
Order By: Relevance
“…Participants that are highly involved with the topic are more likely to engage in systematic processing of the new content than those that are less involved Chaiken 1993, Stamm andDube 1994). We therefore measured participants' perceptions of their involvement in the seminar topic to control for potential dual-process effects, using questions adapted from those used by Stamm and Dube (1994) and adapted by Sussman and Seigal (2003). In prior dual-process studies, involvement, when not manipulated, has tended to be randomly distributed across the sample.…”
Section: Facilities and Proceduresmentioning
confidence: 99%
“…Participants that are highly involved with the topic are more likely to engage in systematic processing of the new content than those that are less involved Chaiken 1993, Stamm andDube 1994). We therefore measured participants' perceptions of their involvement in the seminar topic to control for potential dual-process effects, using questions adapted from those used by Stamm and Dube (1994) and adapted by Sussman and Seigal (2003). In prior dual-process studies, involvement, when not manipulated, has tended to be randomly distributed across the sample.…”
Section: Facilities and Proceduresmentioning
confidence: 99%
“…Although various characteristics of the source that make it believable have emerged from previous research, there is no consensus on a set of credibility dimensions (Self, 1996). Moreover, credibility judgments are contingent upon the type of source being evaluated and the context of the evaluation (Stamm & Dube, 1994). Such contigency suggests that a universal credibility scale is not theoretically useful.…”
Section: Source Credibility and Message Evaluationmentioning
confidence: 99%
“…Because credibility is a receiver assessment and not a source characteristic, audience factors are important determinants of source credibility (Gunther, 1988(Gunther, , 1992. Moreover, credibility is a relational construct in which credibility judgments are contingent on the receiver's relationship to the medium, source, and message (Stamm & Dube, 1994). An audience factor that is particularly relevant to perceptions of credibility within the online medium is Internet experience (Corritore, Kracher, & Wiedenbeck, 2003;Fogg, 2003).…”
Section: Relative Influence Of Message and Structural Featuresmentioning
confidence: 99%
“…Having heavy involvement with an issue has a strong effect on perceptions of credibility (Gunther, 1992;Stamm & Dube, 1994), as does heavy use of the medium in question (Johnson, Kaye, Richard & Wong, 2008;Kiousis, 2001). Studies looking at the message itself have found that credibility can be affected by disorganization and nonfluency in messages (McCrosky & Mehrley, 1969), message intensity (Hamilton & Stewart, 1993), and the writing quality and quantity, (Corrigan & Stephens, 2007;Jackson, 1992;Slater & Rouner, 1996).…”
Section: Introductionmentioning
confidence: 99%